Implanted Radio Telemetry in Orangutan Reintroduction and Post-release Monitoring and its Application in Other Ape Species - Robins, James G.; Husson, Simon; Fahroni, Agus; Singleton, Ian; Nowak, Matthew G.; Fluch, Gerhard; Llano Sanchez, Karmele; Widya, Andhani; Pratje, Peter; Ancrenaz, Marc; Hicks, Nigel; Goossens, Benoit; et al. (Frontiers in Veterinary Science, 2019)
Designed as a new method to facilitate the reintroduction and post-release monitoring of orangutans and other apes, implanted radio-telemetry (IRT) was developed and first deployed in 2009. Since that time, it has been necessary to collate and review information on its uptake and general efficacy to inform its ongoing development and that of other emerging tracking technologies. We present here technical specifications and the surgical procedure used to implant miniaturised radio transmitters, as well as a formal testing procedure for measuring detectable transmission distances of implanted devices. Feedback from IRT practitioners (veterinarians and field managers) was gathered through questionnaires and is also presented. To date, IRT has been used in at least 250 individual animals (mainly orangutans) from four species of ape in both Asia and Africa. Median surgical and wound healing times were 30 minutes and 15 days respectively, with implants needing to be removed on at least 36 separate occasions. Confirmed failures within the first year of operation were 18.1%, while longer distances were reported from positions of higher elevation relative to the focal animal. IRT has been a transformational technology in facilitating the relocation of apes after their release, resulting in much larger amounts of post-release data collection than ever before. It is crucial however, that implant casings are strengthened to prevent the requirement for recapture and removal surgeries, especially for gradually adapting apes. As with all emerging technological solutions, IRT carries with it inherent risk, especially so due to the requirement for subcutaneous implantation. These risks must, however, be balanced with the realities of releasing an animal with no means of relocation, as has historically been, and is still, the case with orangutans and gorillas.